Improving the Marketing Operations Department’s Business Process Efficiency at the Kraft Heinz Company - Jessica Vivi Pribadi (iBuss Management, 2020)
Sales have skyrocketed ever since Kraft Foods and H.J. Heinz merged in 2015. Along with sales, operations costs also rise immensely. The Marketing Operations Department (MOPS) has to cut costs while at the same time deliver value to the company, but this cannot be done as inefficient processes are present. The challenge for MOPS is to address this inefficiency issue while adopting the new company growth plan of standardization into its agenda. Hence, the objective of this report is to propose numerous recommendations to MOPS to improve its business process efficiency and continuously manage the level of efficiency by using Jeston and Nelis’ Business Process Management theory.Interviews with relevant resources in the marketing projects, personal observation during the work placement, analysis of internal data, and online and offline literature review have helped concluded some notable recommendations: working with the internal communications department to communicate the proposed changes, creating a guidebook explaining the complete process of MOPS, creating an online share point containing all files, having an inhouse artwork designer with possible savings of 30% from annual costs, developing a merged tool combining three major platforms of MOPS, and eliminating redundant, unnecessary phases or tasks within the MOPS process.Keywords: Business Process Efficiency Improvement, Business Process Management, Marketing Operations, Cost-cutting Practices